Exercise reduces immune suppression and breast cancer progression in a preclinical model - Wennerberg, Erik (Oncotarget, 2020)
Exercise is associated with favorable changes in circulating immune cells and improved survival in early-stage breast cancer patients, but the mechansims remain to be fully elucidated. Preclinical studies indicate that physical activity started before tumor injection reduces tumor incidence and progression. Here we tested whether exercise has anti-tumor effects in mice with established 4T1 mammary carcinoma, a mouse model of triple negative breast cancer. Exercise slowed tumor progression and reduced the tumor-induced accumulation of myeloid-derived suppressor cells (MDSCs). The reduction in MDSCs was accompanied by a relative increase in natural killer and CD8 T cell activation, suggesting that exercise restores a favorable immune environment. Consistently, exercise improved responses to a combination of programmed cell death protein 1 (PD-1) blockade and focal radiotherapy. These data support further investigations of exercise in breast cancer patients treated with combinations of immunotherapy and cytotoxic agents to improve cancer outcomes.